MOBILE MONEY SERVICES AND FINANCIAL ACCESSIBILITY; ACASE STUDY OF UGANDA CHRISTIAN UNIVERSITY - BOBOLI SIMON (UGANDA CHRISTIAN UNIVERSITY, 2025)
The study assessed the relationship between mobile money services and financial accessibility of Mobile money users pursuing bachelors of business administration in Uganda Christian University. The study was conducted in consideration of three key objectives that guided it, they include; examining the factors that influence mobile money usage, assessing the relationship between mobile money services and financial accessibility and identifying the challenges face by students in using mobile money and suggest possible solutions. The research employed cross-sectional research design and with the use of only quantitative research approach. Structured questionnaires were used for data collection from a sample of 60 respondents, the researcher employed simple random sampling technique to select the desired respondents from the different areas of specialization like accounting, finance, marketing and management. Data was collected, coded and analyzed using statistical tools like SPSS to obtain insight into the responses and draw reasonable and meaningful conclusions. Findings revealed that mobile money services and financial accessibility has a strong positive correlation meaning that there is a strong relationship between mobile money services and accessibility to financial services and key challenges encountered by users include; network challenges, high transaction charges and security issues like fraud, Finally, the study revealed that there is a strong relationship between mobile money services and financial accessibility implying that mobile money services enhance individuals’ ability to access, save, transfer, receive and generally use financial services effectively and recommends an Improvement in network infrastructure, reduction in the transaction fees, ensuring the customer deposits are protected through enhancing security and reversal services.
UNDERGRADUATE RESEARCH